Study of possibilities pelletizing cocoa shell Ecuador and their use as biofuel - Velazquez-Araque, Luis; Cárdenas Murillo, Jose; Carrillo, Vicente; Valenzuela, Jhonathan (Revista Universidad de Guayaquil, 2015)
In Ecuador, there is a constant need to generate electric and thermal energy, also global warming caused by increased emissions of greenhouse gases and the pursuit of energy independence, have created a new industry focused on energy generation by harnessing renewable sources. Biomass is established as the third leading source for producing electricity as the main source for the generation of thermal energy. However, the problems related to the low density of the different types of biomass and the difficulty in carrying and storing have caused the need to generate solids with higher density and stronger hardness known as pellets and briquettes. This paper develops an analysis of the possibilities for pelletizing the Ecuadorian cocoa pod husk and its use as biofuel. Several pellets configurations were proposed based on the diameter and length ratio. An experimental setup was established to crush and screen the cocoa pod husk in order to obtain less than 1.5 mm particle size. Then the pellets were made using a small scale pellet machine and finally burned in a combustion chamber for the evaluation of the energy potential by means of the high heat value and ash content. Finally, the selection of the most energy efficient pellet configuration is made taking into consideration international pellet quelite standards as well. This large-scale project would represent a cost savings in the Ecuadorian industrial sector leading further to lowering smog emissions into the environment from burning fossil fuels and also it would prevent the cocoa pod husk as a focus for the spread of Phytophthora species which is a main cause of economic losses in the cocoa industry.
Keywords: biomass; cocoa shell; biofuels; greenhouse; pellets